Harmoni Persatuan dalam Perbedaan : Problematika Pernikahan Lintas Organisasi NU Dan Muhammadiyah Dalam Bahtera Rumah Tangga (Studi Kasus di Tegal) - sari, Isma; Sairin, Novi Asmaul Khasanah; Hami, Widodo (Fakta: Forum Aktual Ahwal Al-Syakhsiyah, 2023)
This research discusses the challenges of harmonious unity in differences in cross-organizational marriages between Nahdlatul Ulama (NU) and Muhammadiyah within the household. The main focus of the research is to understand the impact of different views of religious organizations on the dynamics of relationships and interactions between couples from NU and Muhammadiyah organizations. With a qualitative approach, this research involves in-depth interviews and observations of couples who face this problem. The research results show that differences in principles and values ​​between NU and Muhammadiyah can create tension in the household, requiring more intense open communication and the ability to manage differences wisely. This research also highlights the importance of an inclusive approach and mutual respect to strengthen harmony in households across religious organizations. The implications of these findings can contribute to efforts to understand the dynamics of marriage across organizations and design interventions that support the sustainability of unity despite differences in society.Keeyword : Harmony, Marriage, Cross-organization.